Upaya kepala sekolah dalam meningkatkan prospek kerja sama sekolah dengan industri di era 5G - Febi Akbar Rizki; Rina Mida Hayati; Atika Fadilatul Rodiyah Saputri (Kuras Institute, 2025)
Purpose − This research aims to examine the role of school principals in enhancing school-industry cooperation in the era of 5G technology. The 5G era brings great changes in education, especially vocational education, by providing fast connectivity and advanced technology for digital learning. Method − This research uses a descriptive qualitative approach through interviews, observations, and literature studies. The focus is on the principal's strategy in establishing partnerships with industry to prepare graduates that meet the needs of the labor market Findings − The results show that principals play an important role as facilitators and innovators in building relationships with industry. The strategies implemented include curriculum development based on industry needs, technology training for teachers, and the use of 5G technology to support internship programs and digital learning. Obstacles faced include limited infrastructure, lack of technological understanding, and bureaucratic obstacles in cooperation with industry.